Quality of life and wellbeing among breast cancer patients in Lahore, Pakistan - Ayub, Fiza; Khan, Tahir Mehmood; Baig, Mirza Rafi; Amin, Muhammad Usman; Tahir, Humera (Frontiers in Oncology, 2023)
Background Breast cancer has a high incidence rate, emphasizing the necessity of enhanced information on health-related quality of life (HrQOL) in this population of patients. The aim of this study was to identify the factors influencing the QOL experienced by patients in Pakistan. Methods A cross-sectional study was conducted on women with breast cancer, and four instruments were used on a random sample of 130 Pakistani women: FACIT-B Version 4 questionnaire,WHO causality assessment scale, Naranjo’s algorithm, and a demographic/clinical characteristics section. Data analysis included descriptive analysis, independent sample t-test, and analysis of variance (ANOVA) test. Results The patients’ mean age was 49.10 (standard deviation (SD) 10.89); 98.5% were married. The mean score was 18.34 for physical wellbeing (SD 5.92; interquartile range (IQR) 11), 16.33 for social/family wellbeing (SD 6.3; IQR 11.25), 13.6 for emotional wellbeing (SD 3.55; IQR 6), 17.13 for functional wellbeing (SD 3.73; IQR 6), and 24.86 for breast cancer subscale (SD 3.64; IQR 4). The study found that the age, entitlement, recurrence, marital status, salary, number of doses, duration of cancer treatment, and chemotherapy sessions were significantly related to QOL terms in the assessment of the FACIT-B scale. The WHO causality evaluation scale determined that 78.1% of the responses were “probable” and 20.1% were “possible”. According to Naranjo’s algorithm assessment scale, 80% of adverse drug reactions (ADRs) were “probable”, whereas 18.4% were declared “possible”. Chemotherapy-induced anemia was the most often reported ADR in 64.6% of patients, followed by chemotherapy-induced nausea and vomiting (61.5%). Conclusion Healthcare practitioners must acknowledge and take into account the significance of QOL in addition to therapy for breast cancer patients in order to enhance their health. The findings of this study will aid in filling gaps in current unknown knowledge and identifying sites where patients require additional assistance. Because cancer and chemotherapy clearly have a negative impact on individuals’ QOL, oncologists must concentrate on strategies that help cancer patients during their sickness and treatment while also enhancing self-care and QOL. Those with cancer will benefit from emotional wellbeing and adaptation to their disease.